Immune Activity of Vannamei Shrimp (Litopenaeus vannamei) Under Ozonated and Non-Ozonated Treatments - Moh. Wildanul Jannah; Asus Maizar Suryanto Hertika; Yenny Risjani; Wahidah Inayati (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effect of ozonation treatment on the immune activity of vannamei shrimp, compared to non-ozonization treatment. Parameters measured include Total Haemocyte Count (THC), Differential Haemocyte Count (DHC), and phagocytic activity. The results show that ozonation treatment produces higher THC values, namely an average of 75% more than non-ozonation. The DHC value in the ozonation treatment showed an increase in granular cells by 40% compared to the non- ozonation treatment. In contrast, hyaline cells decreased due to a more active immune response against pathogens. Phagocytic activity in the ozonation treatment reached 15%, higher than non-ozonization which only reached 10.33%. These data indicate that ozonation plays an important role in improving shrimp's immune response by reducing the water's pathogen content and minimizing stress. In conclusion, ozonation was proven effective in increasing the immunity of vannamei shrimp by supporting key immunological parameters.